EFFECTIVENESS INTEGRATION OF THE EXAMPLE NON EXAMPLE MODEL ASSISTED BY AUDIOVISUAL MEDIA TO INCREASE MOTIVATION AND LEARNING OUTCOMES OF IPAS AT SDN 2 KEPUTRAN - Mindarwati, Yunita Esti; Herwin, Herwin (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study examines the effectiveness of the integration of the example non example model assisted by audiovisual media to increase motivation and learning outcomes of IPAS at SDN 2 Keputran. The problem stems from the low student participation (35%) and completeness of IPAS learning outcomes (40%) due to the dominance of the teacher-centered approach. Using the methodology of Classroom Action Research Kemmis and McTaggart's model, the research involved 24 fourth-grade students with data collection through participatory observation, cognitive tests, motivation questionnaires, and documentation. The results showed a significant increase in learning motivation from a score of 61.67 (preaction) to 82.92 (cycle II), as well as an increase in the completeness of learning outcomes from 33.3% to 100% with an average score from 61.67 to 82.89. The integration of the example non example model with audiovisual media succeeded in creating an active and meaningful learning environment, activating high-level cognitive processes through dynamic visualization and comparative activities. In conclusion, this pedagogical approach effectively deconstructs the teacher-centered paradigm into student-centered learning, significantly contributing to transforming students' learning experience in the context of 21st-century education.